Organizacja opieki i pomocy osobom, wobec których podjęto interwencję policyjną - Stankiewicz, Adam; Magda, Ernest (Wydawnictwo Naukowe EDUsfera, 2022)
The course of an intervention determined by the nature of an event, care and assistance to people in need may dominate the aim of police actions. Providing security to citizens and protecting their lives, health, and property materialise most fully in local communities, where a police officer is required to go beyond the framework of legal protection.
Keywords: care; assistance; police intervention